Detection of Quorum Sensing Genes of Pseudomonas aeruginosa Isolated from Different Areas in Iraq - Mohammed, Huda Abbas; Zgair, Ayaid Khadem (Iraqi Journal of Science, 2022)
Pseudomonas aeruginosa is an opportunistic pathogen. Quorum sensing (QS) is one of processes that are responsible for biofilm formation. P. aeruginosa can live in different environments, some of which are pathogenic (clinical isolates) and some that are found outside the body (environmental isolates). The present study aimed to determine the presence of a number of genes responsible for QS in clinical and environmental isolates of P. aeruginosa. In the present study full DNA was separated from all environmental and clinical isolates that contained seven genes (rhlA, rhlR, rhlI, lasR, lasI, lasB, phzA1) associated with QS occurrence. The total DNA was separated from all environmental and clinical isolates (PAE1, PAE2, PAE3, PAE4, PAE5, PAE6, PAE7, PAE8, PAE10, PAE11, PAE12, PAE14, PAC1, PAC2, PAC5, PAC7, PAC8, PAC9 and PAC10). This study found that all studied environmental and clinical isolates contained the seven genes rhlA, rhlR, rhlI, lasR, lasI, lasB, phzA1, which was associated with QS occurrence.